2021
DOI: 10.1007/s11240-021-02181-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration of the endangered cactus Turbincarpus mombergeri (Riha), a hybrid of T. laui × T. pseudopectinatus

Abstract: Turbinicarpus mombergeri is a cacti species formed by a hybridization process between Turbinicarpus laui and Turbinicarpus pseudopectinatus. Under natural conditions, it is very di cult for two species be genetically compatible for hybridization, and to produce owers at the same time. Thus, T. mombergeri is a very interesting and a rare species. Unfortunately, the current populations are decreasing and now it is considered critically endangered. The aim of this research was to develop a successful protocol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, for some woody species, the effect of MS medium is negative because of its high levels of ammonium ions [33]. Many studies have indicated that the incidence of hyperhydricity can be minimized by reducing the salt concentration of the medium, especially for endangered plants [34]. Our results showed the growth and proliferation of buds to be much higher on MSM, in which the concentrations of ammonium nitrogen (1280 mg/L) and nitrate nitrogen (2800 mg/L) were moderate.…”
Section: Effects Of Basal Mediummentioning
confidence: 99%
“…However, for some woody species, the effect of MS medium is negative because of its high levels of ammonium ions [33]. Many studies have indicated that the incidence of hyperhydricity can be minimized by reducing the salt concentration of the medium, especially for endangered plants [34]. Our results showed the growth and proliferation of buds to be much higher on MSM, in which the concentrations of ammonium nitrogen (1280 mg/L) and nitrate nitrogen (2800 mg/L) were moderate.…”
Section: Effects Of Basal Mediummentioning
confidence: 99%
“…To date, in vitro shoot propagation or asymbiotic seed germination is considered a reliable method for the conservation of orchids (Hoang et al 2016;Pujasatria et al 2020;Santos-Díaz et al 2022). Especially the number of explants that are available for in vitro conservation projects can be seasonal or very limited in quantity (Sarasan 2010).…”
Section: Introductionmentioning
confidence: 99%